2020
DOI: 10.1248/cpb.c19-01108
|View full text |Cite
|
Sign up to set email alerts
|

Development of Photoswitchable Estrogen Receptor Ligands

Abstract: Photopharmacology has attracted attention as an approach for the development of novel therapeutics because it allows regulation of the bioactivity of compounds based on their conformational change by photo-irradiation. Previously, we have reported several types of selective estrogen receptor (ER) modulators based on diphenylmethane skeleton. To develop novel photopharmacological reagents, we designed and synthesized a set of ER ligands based on azobenzene skeleton, which can switch its conformation following U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Subsequently, we developed a photohormone for the bile acid receptor farnesoid X receptor (FXR) that allows for the optical control of gene regulation in liver cells. In addition, a photoswitchable estrogen receptor (ER) agonist was recently reported by Tsuchiya. , Here, we disclose the development of photohormones for PPARγ, extending the reach of photopharmacology to another important member of the NHR superfamily.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Subsequently, we developed a photohormone for the bile acid receptor farnesoid X receptor (FXR) that allows for the optical control of gene regulation in liver cells. In addition, a photoswitchable estrogen receptor (ER) agonist was recently reported by Tsuchiya. , Here, we disclose the development of photohormones for PPARγ, extending the reach of photopharmacology to another important member of the NHR superfamily.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, a photoswitchable estrogen receptor (ER) agonist was recently reported by Tsuchiya. 28,29 Here, we disclose the development of photohormones for PPARγ, extending the reach of photopharmacology to another important member of the NHR superfamily.…”
Section: ■ Introductionmentioning
confidence: 99%
“… [42] This photolipid successfully modulated FXR‐dependent gene expression in non‐transfected liver cells with light. Recently, a photoswitchable estrogen receptor ligand was developed ( 9 ) [43] . It exhibited different binding profiles in the presence and absence of UV‐A light as assayed by fluorescence polarization.…”
Section: Nuclear Hormone Receptorsmentioning
confidence: 99%
“…Recently, a photoswitchable estrogen receptor ligand was developed (9). [43] It exhibited different binding profiles in the presence and absence of UV-A light as assayed by fluorescence polarization.…”
Section: G Protein-coupled Receptorsmentioning
confidence: 99%
“…This could indeed be demonstrated with a few classes of NRs, including retinoic acid receptor α (RARα), which can be optically controlled by a photoswitchable retinoic acid derivative . Subsequently, we have developed dedicated photohormones for the bile acid-activated transcription factor farnesoid X receptor (FXR) and the fatty acid-sensing peroxisome proliferator-activated receptor γ (PPARγ), and Tsuchiya et al have reported a photoswitchable estrogen receptor (ER) agonist . Still, in light of their value as chemical tools for pharmacology, the collection of available photoswitchable ligands for transcription factors is scarce.…”
Section: Introductionmentioning
confidence: 99%